Helicobacter pylori and epithelial mesenchymal transition in human gastric cancers: An update of the literature - Tala M. Jamal Eddin (17012235) (2023)
Gastric cancer, a multifactorial disease, is considered one of the most common malignancies worldwide. In addition to genetic and environmental risk factors, infectious agents, such as Epstein-Barr virus (EBV) and Helicobacter pylori (H.pylori) contribute to the onset and development of gastric cancer. H. pylori is a type I carcinogen that colonizes the gastric epithelium of approximately 50% of the world's population, thus increasing the risk of gastric cancer development. On the other hand, epithelial mesenchymal transition (EMT) is a fundamental process crucial to embryogenic growth, wound healing, organ fibrosis and cancer progression. Several studies associate gastric pathogen infection of the epithelium with EMT initiation, provoking cancer metastasis in the gastric mucosa through various molecular signaling pathways. Additionally, EMT is implicated in the progression and development of H. pylori-associated gastric cancer. In this review, we recapitulate recent findings elucidating the association between H. pylori infection in EMT promotion leading to gastric cancer progression and metastasis. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2023.e18945